FACTORS AFFECTING CONSUMER SATISFACTION IN THE COFFEE INDUSTRY. - Prioko, Ohlala Ahrinawangi; Noveriandi, Namira Ramadhani; Natalia, Shun Fitriani (Economic Faculty, Attahiriyah Islamic University, 2020)
This study aims to determine the quality of service and to determine the level of satisfaction and to determine the effect of service quality on customer satisfaction in the Coffee Industry. The research method used is explanatory. Based on research and data analysis that has been done, it is found that the quality of service contributes an effect of 73.1% to the formation of Bekasi Post Coffee Station customer satisfaction. The benefits of this study are that the results of the average value of respondents' responses to all indicators of service quality have been well received by consumers of Post Coffee Station Bekasi regarding products and services they have.